Discovery of naturally occurring transmissible chronic hepatitis B virus infection among Macaca fascicularis from mauritius island. Issue 5 (17th September 2013) - Dupinay, Tatiana; Gheit, Tarik; Roques, Pierre; Cova, Lucyna; Chevallier‐Queyron, Philippe; Tasahsu, Shin‐i; Le, Roger; Simon, François; Cordier, Geneviève; Wakrim, Lahcen; Benjelloun, Soumaya; Trépo, Christian; et al.
<x xml:space="preserve">Abstract</x> Despite a high prevalence of hepatitis B virus (HBV) infection in endangered apes, no HBV infection has been reported in small, old‐world monkeys. In search for a small, nonhuman primate model, we investigated the prevalence of HBV infection in 260 macaque (Cercopithecidae) sera of various geographical origins (i.e., Morocco, Mauritius Island, and Asia). HBV‐positive markers were detected in cynomolgus macaques (Macaca fascicularis) from Mauritius Island only, and, remarkably, HBV DNA was positive in 25.8% (31 of 120) and 42% (21 of 50) of serum and liver samples, respectively. Strong liver expression of hepatitis B surface antigen and hepatitis B core antigen was detected in approximately 20%‐30% of hepatocytes. Furthermore, chronic infection with persisting HBV DNA was documented in all 6 infected macaques during an 8‐month follow‐up period. Whole HBV genome‐sequencing data revealed that it was genotype D subtype ayw3 carrying substitution in position 67 of preS1. To confirm infectivity of this isolate, 3 Macaca sylvanus were inoculated with a pool of M. fascicularis serum and developed an acute HBV infection with 100% sequence homology, compared with HBV inoculum. We demonstrated the presence of a chronic HBV infection in M. fascicularis from Mauritius Island. This closely human‐related HBV might have been transmitted from humans, because the initial breeding colony originated from very few ancestors 300 years ago when it was implemented by Portuguese who imported a handful of macaques from Java to Mauritius Island. Conclusion: This report on natural, persisting HBV infection among cynomolgus macaques provides the first evidence for the existence of a novel, small simian model of chronic HBV infection, immunologically close to humans, that should be most valuable for the study of immunotherapeutic approaches against chronic hepatitis B. (Hepatology 2013;58:1610–1620)